« Beautiful Idiots and Brilliant Lunatics » Social Comedy, Nostalgia and a World of Fantasy (Wilde and Hofmannsthal) - Anne-Isabelle François (Cahiers Victoriens et Edouardiens)
The article focuses on the social comedies where a reception is being held, these passages offering a key to understanding not only the lasting popularity of the productions, but also the symbolic value and general ambivalence of Wilde’s theatrical picture of the Victorian upper class. The acts present an extremely brilliant, though exaggerated mirror world and act thus as critical comments upon the fabric of British society, a glowing Schein on the brink of disappearing forever. Wilde’s stagecraft lies in his combination of the codes of sociability and the codes of comedy, revealing the theatrical nature of Victorian high society, even the universal shaming of these “beautiful idiots and brilliant lunatics”. The author compares Wilde’s comedies with another pièce de salon and conversation piece, functioning as révélateur, Hugo von Hofmannsthal’s Der Schwierige (1921), also a lasting success while set in an era radically out of touch with the present. The article offers thus a comparative perspective on the model of sociability exhibited by the reception scenes, a model no longer valid if it even has ever existed as such, and stresses its fundamental and underlying element of melancholy. What the public is made to witness is perhaps only a graceful though extremely attractive ballet of ghosts and masks, long lost, but still striking a most powerful chord—one of the reasons for the plays’ enduring success : they appeal to modern audiences’ fantasy and work, paradoxically, as founding myths of the Ideal Victorian or Austro-Hungarian aristocratic society.